2018
DOI: 10.1007/s11605-018-3783-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Discharge Timing on Readmission Following Hepatopancreatobiliary Surgery: a Nationwide Readmission Database Analysis

Abstract: Early discharge after HPB surgery was not associated with increased 30- or 90-day readmission. Overall 90-day in-hospital mortality following a readmission was comparable among patients with an early, routine, and late discharge, while median charges were lower in the early discharge group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In patients who underwent major and minor liver resection, the median hospital stays were 9 and 7 days, respectively, and 30-day readmission rates were 17.8% and 7%, respectively. These numbers are comparable with registry data on hepatopancreatobiliary surgery from the United States, where 7-day hospital stays and 17% readmission rates were reported (27). In all, 30.1% of minor pancreatic resections were done in a minimally invasive manner, a notably high rate taking into account that the first laparoscopic pancreatic resection was done at our center in 2007.…”
Section: Discussionsupporting
confidence: 85%
“…In patients who underwent major and minor liver resection, the median hospital stays were 9 and 7 days, respectively, and 30-day readmission rates were 17.8% and 7%, respectively. These numbers are comparable with registry data on hepatopancreatobiliary surgery from the United States, where 7-day hospital stays and 17% readmission rates were reported (27). In all, 30.1% of minor pancreatic resections were done in a minimally invasive manner, a notably high rate taking into account that the first laparoscopic pancreatic resection was done at our center in 2007.…”
Section: Discussionsupporting
confidence: 85%
“…Examining data obtained from the Surveillance, Epidemiology, and End Results-Medicare linked database, Stitzenberg et al 29 reported that roughly 13%-15% of patients who had a range of cancer operations were discharged to a SNF. In a separate study that focused only on patients who underwent hepatopancreatobiliary surgery, Merath et al 30 noted that approximately 5%-6% of patients had a postdischarge admission to a SNF. In the current study, the utilization of a SNF was much greater at 17%.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the greater incidence of SNF utilization in the current study was undoubtedly multifactorial and likely related to differences in the underlying patient cohort. For example, unlike the study by Merath et al 30 that included patients of all ages who underwent either liver or pancreatic procedures, the current study included only patients who were 65 years of age or older and had undergone pancreatic resection. The older patient cohort, as well as the focus on pancreatic procedures that can be associated with complications, such as fistula and delayed gastric emptying, likely explain the greater SNF utilization in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the analysis of individual outcome measures, such as mortality, morbidity, length of stay (LOS), and readmission, has advantages, composite benchmarks of surgical quality may be more relevant and helpful. [2][3][4][5][6][7][8] In particular, data on a single indicator do not reflect the whole surgical process and may not reliably measure overall hospital quality. [9][10][11][12] Composite measures combine information from multiple domains into a single summary measure and therefore may be superior to individual measures for the analysis of hospital performance.…”
mentioning
confidence: 99%